Change in Sucrose Cleavage Pattern and Rapid Starch Accumulation Govern Lily Shoot-to-Bulblet Transition in vitro - Wu, Yun; Ren, Ziming; Gao, Cong; Sun, Minyi; Li, Shiqi; Min, Ruihan; Wu, Jian; Li, Danqing; Wang, Xiuyun; Wei, Yanping; Xia, Yiping (Frontiers in Plant Science, 2021)
In bulb crops, bulbing is a key progress in micropropagation and is the feature that most distinguishes bulbous crops from other plants. Generally, bulbing involves a shoot-to-bulblet transition; however, the underlying mechanism remains elusive. We explored this process by tracking the shoot-to-bulblet transition under different culture conditions. Rapid starch accumulation occurred at 15 days after transplanting (DAT) in the bulblet-inducing treatments as confirmed via histological observations and the significant elevation of starch synthesis related-gene transcription, including LohAGPS, LohAGPL, LohGBSS, LohSS, and LohSBE. However, for shoots that did not transition to bulblets and maintained the shoot status, much higher soluble sugars were detected. Interestingly, we observed a clear shift from invertase-catalyzed to sucrose synthase-catalyzed sucrose cleavage pattern based on the differential expression of LohCWIN and LohSuSy during the key transition stage (prior to and after bulbing at 0-15 DAT). Shoots that transitioned into bulblets showed significantly higher LohSuSy expression, especially LohSuSy4 expression, compared with shoots that did not transition. A symplastic phloem unloading pathway at the bulblet emergence stage (15 DAT) was verified via the 6(5)-carboxyfluorescein diacetate fluorescent tracer. We propose that starch is the fundamental compound in the shoot-to-bulblet transition and that starch synthesis is likely triggered by the switch from apoplastic to symplastic sucrose unloading which may be related to sucrose depletion. Furthermore, this study is the first to provide a complete inventory of the genes involved in starch metabolism based on our transcriptome data. Two of these genes, LohAGPS1.2b and LohSSIIId, were verified by rapid amplification of cDNA ends cloning, and these data will provide additional support for Lilium research since whole-genome are currently lacking.